RELIGION AND FINANCE: THE CASE OF ISLAMIC EQUITY INDICES - El Khatib, Ahmed Sameer; Lisboa, Nahor Plácido (REUNIR Revista de Administração Contabilidade e Sustentabilidade, 2019)
Despite the increasing attention to ethical investments, the empirical studies on Islamic indices are scarce. The principles of Islamic indices are similar to those of other ethical indices in terms of the screening process; both of them are also characterized by their short histories. So, after Islamic indices were introduced in the late nineties, many financial markets and index providers launched their own Islamic indices for investors looking for investment opportunities without compromising their beliefs. Analysing the financial performance of Islamic equity indices from all relevant providers, we document these indices to outperform their conventional benchmarks on a global and developed market level after controlling for investment styles and a potential back-testing bias. To explain this outperformance puzzle, we investigate fundamental (i.e., risk factors), behavioural (i.e., Ramadan) and research design (i.e., sample length) related explanations but the overall results persist. When eliminating the effect of the financial services industry from conventional benchmarks, however, the outperformance of all indices except the Dow Jones Islamic Market (DJIM) world index disappears. This implies that Islamic equity indices have outperformed due to their critical position towards risk-free interest and the financial services industry. We conclude that they represent a viable alternative for risk-averse passive investors, especially during periods of high uncertainty around financial services. Further research is needed to fully understand the abnormally good performance of the DJIM.